Effect of surface-treated silica nanofluid on supercritical CO2 injection efficiency: Application to deep saline aquifers - Seokgu Gang; Ingu Kang; Jeonghwan Lee; Jongwon Jung (Journal of CO2 Utilization)
Deep saline aquifers are well-established as highly suitable for geological carbon sequestration because of their significantly greater storage capacity than other storage layers, such as depleted gas or oil reservoirs and coal seams. The use of additives, including surfactants and nanofluids, has been identified as a promising approach to mitigate the reduction in injection and storage efficiency caused by capillary forces between immiscible fluids in porous media during carbon dioxide injection into deep saline aquifers. This study analyzed the interfacial tension and wettability (contact angle) characteristics of carbon dioxide in the presence of nanofluids containing surface-treated SiO2-based nanoparticles. The injection characteristics were also evaluated through experimental and numerical methods using micromodels and pore network modeling. The results indicate that nanofluids effectively reduce interfacial tension and enhance wettability. Injection efficiency increased as the nanofluid concentration increased from 0 wt% to 1 wt% under low supercritical CO2 injection velocity conditions, with a slight upward trend observed at higher concentrations. Sensitivity analysis conducted via pore network modeling revealed that the injection efficiency was more significantly influenced by interfacial tension than by wettability. Furthermore, the injection efficiency improvements observed in the numerical models were closely aligned with the trends observed in the micromodel experiments. These results demonstrate that the surface-treated SiO2 based nanofluids used in this study can significantly enhance the injection efficiency of geological carbon sequestration.